1987
DOI: 10.1161/01.hyp.10.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional consequence of neonatal sympathectomy on the blood vessels of spontaneously hypertensive rats.

Abstract: SUMMARY Neonatal sympathectomy of spontaneously hypertensive rats (SHR) and control Wistar-Kyoto rats (WKY) was performed by a combined treatment with antiserum to nerve growth factor and guanethidine during the first 4 weeks after birth. The development of hypertension was completely prevented in the treated SHR: at 28 to 30 weeks of age, systolic blood pressure of treated SHR was 139 ± 2 mm Hg as compared with 195 ± 8 mm Hg in untreated SHR. The extent of sympathectomy was verified by histofluorescence. Fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
89
0
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 52 publications
6
89
0
1
Order By: Relevance
“…An early increase of LV weight was also observed in SHR of the present study, and previous reports have demonstrated that sympathetic nerve stimulation might play an important role in early stage LV hypertrophy (14,15). Furthermore, Dang et al (16) showed that LV tissue angiotensin-II concentrations were significantly higher in SHR than in WKY from 15 to 28 weeks of age, although plasma angiotensin-II levels were similar in both groups.…”
Section: Discussionsupporting
confidence: 79%
“…An early increase of LV weight was also observed in SHR of the present study, and previous reports have demonstrated that sympathetic nerve stimulation might play an important role in early stage LV hypertrophy (14,15). Furthermore, Dang et al (16) showed that LV tissue angiotensin-II concentrations were significantly higher in SHR than in WKY from 15 to 28 weeks of age, although plasma angiotensin-II levels were similar in both groups.…”
Section: Discussionsupporting
confidence: 79%
“…A sensory function has been suggested for SP in the vascular nerves, 1 yet, neonatal treatment of spontaneously hypertensive rats (SHR) with capsaicin, which presumably depletes neuronal SP, also prevented hypertension development in these rats, 2 suggesting SP may have other functions besides a sensory function. In our recent study on the effect of sympathectomy on hypertension development and vessel wall morphology, 3 we found that despite the destruction of sympathetic nerves with our procedure, other nerve types were still present.The primary aim in our present study was to locate and identify various peptide-containing nerves from the cerebral and peripheral blood vessels of stroke-prone SHR (SHRSP) and Wistar-Kyoto rats (WKY). Our intent was to relate the distribution of these nerves to the known action of the peptides so that we could gain some understanding concerning the possible involvement of these nerves in the development of hypertension.…”
mentioning
confidence: 58%
“…A sensory function has been suggested for SP in the vascular nerves, 1 yet, neonatal treatment of spontaneously hypertensive rats (SHR) with capsaicin, which presumably depletes neuronal SP, also prevented hypertension development in these rats, 2 suggesting SP may have other functions besides a sensory function. In our recent study on the effect of sympathectomy on hypertension development and vessel wall morphology, 3 we found that despite the destruction of sympathetic nerves with our procedure, other nerve types were still present.…”
mentioning
confidence: 58%
See 2 more Smart Citations